Strategic Management and Digital Literacy: Enhancing Teacher Pedagogical Competence in the Digital Era - Karmin, Karmin; Rosani, Meilia; Pahlawan, Pahlawan (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines (1) the strategic management of digital literacy for educators at SMP Negeri 3 Lempuing, (2) the process of teacher digital literacy development in the digital era, and (3) the influence of digital literacy on pedagogical competence enhancement. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and documentation, supplemented by secondary data. Data analysis followed an interactive model, with validity ensured via triangulation (source, theory, method) and referential adequacy. Findings indicate that digital literacy strategy management adheres to the POAC framework (Planning, Organizing, Actuating, Controlling). Planning involves objective-setting, resource allocation, and success metrics; organizing focuses on HR management and government collaboration; implementation includes digital platform training, online safety education, and positive content creation; and control is maintained through monitoring and evaluation. Pedagogical competence improvement follows the I-P-O model (Input-Process-Output), where inputs (student characteristics, funding) and processes (ed-tech design, strategic management) yield outputs (student achievement, institutional recognition). The study also identifies internal impacts (family influence, school infrastructure) and external impacts (internet access, cyber risks like fraud and bullying). This research is among the first to integrate POAC strategic management and I-P-O frameworks in analyzing digital literacy’s role in pedagogical development, offering a structured approach for educational institutions navigating digital transformation. Schools should adopt structured digital literacy programs, foster government partnerships, and implement continuous monitoring to mitigate cyber risks while enhancing teacher competence. The study provides a model for digital literacy strategy management in education, highlighting its critical role in improving teaching quality and institutional readiness for digital-era challenges.